Pengaruh Praktik Corporate Governance dan Prinsip Konservatisme Terhadap Manajemen Laba (Study Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - ramsah, Hasnawati; Agus Sutarjo; Meri Yani (Fakultas Ekonomi, Universitas Ekasakti, 2023)
In this study, the multiple linear regression method was used for data analysis. The purpose of this study was to analyze the impact of institutional ownership, management ownership, independent commissioners, audit committees, and conservatism on financial management. The subjects of this research are companies listed on the Indonesia Stock Exchange for the period 2018-2019 in the manufacturing category. And obtained 23 research samples using the purposive sampling method. The results of this study indicate that institutional ownership, management, independent commissioners, audit committees, and conservatism do not affect profit management.